1997
DOI: 10.3177/jnsv.43.83
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Lipids and Incidence of Cerebral Infarction in a Japanese Rural Community.

Abstract: SummaryObjective: To assess the relationship between dietary lipids and incidence of cerebral infarction in a Japanese rural population. Design: A cohort study from July 1977 through December 1992. Setting: Akadani-Ijimino (A-I) district, Niigata Prefecture, Japan. Subjects and methods: All the residents, 1,182 men and 1,469 women, aged 40 years and over. Out of these members, 954 men and 1,329 women who were initially free of stroke completed a semiquantitative food frequency ques tionnaire in 1977, and were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 34 publications
1
33
0
Order By: Relevance
“…However, differences in some other biological, socioeconomic, or lifestyle factors (diet in particular) may influence such an association; for example, the fat intake of the elderly is lower than that of younger people. 50 Carriers of the ⑀2 allele may have a greater chance of endothelial weakening in intracerebral arteries because of lower cholesterol levels, 36 whereas the diminished impact of the ⑀4 allele on LDL levels in elderly groups 51 may also explain our findings of a decreased association between ⑀4 and stroke in elderly subjects. Such age-dependent changes in the association of the ⑀2 or ⑀4 alleles with stroke have also been suggested in previous studies.…”
Section: Discussionsupporting
confidence: 39%
“…However, differences in some other biological, socioeconomic, or lifestyle factors (diet in particular) may influence such an association; for example, the fat intake of the elderly is lower than that of younger people. 50 Carriers of the ⑀2 allele may have a greater chance of endothelial weakening in intracerebral arteries because of lower cholesterol levels, 36 whereas the diminished impact of the ⑀4 allele on LDL levels in elderly groups 51 may also explain our findings of a decreased association between ⑀4 and stroke in elderly subjects. Such age-dependent changes in the association of the ⑀2 or ⑀4 alleles with stroke have also been suggested in previous studies.…”
Section: Discussionsupporting
confidence: 39%
“…32 Small vessel pathogenesis differs from the atheroma process in large vessels, and cholesterol may protect small vessel endothelium. 29,32,33 Thus, in the Honolulu Heart Program study, protein and fat from animal sources were risk factors for atherosclerosis in large arteries, but not in the small cerebral vessels. 28 Nevertheless, in spite of accumulated data on the protective effect of blood cholesterol level on stroke incidence or death, 34,35 we did not observe any significant correlation between dietary cholesterol and total serum cholesterol levels (correlation coefficientϭϪ0.01, Pϭ0.40).…”
Section: Discussionmentioning
confidence: 99%
“…Third, in a 14-y prospective study (1983 to 1997) of 4,775 Japanese aged 40 to 69 y who participated in a single 24-h dietary recall survey, a low intake of saturated fat (approximately ,10 g/d) was found to be associated with increased risk of intraparenchymal hemorrhage after adjusting for known cardiovascular risk factors (7). No study found an association between saturated fat intake and risk of brain infarction (10).…”
Section: Saturated Fat 2-1 Dg (Lower Boundary)mentioning
confidence: 99%
“…Observation of elevated mortality from intracerebral hemorrhage in patients with lower blood cholesterol concentrations does not confirm that low blood cholesterol concentration is a cause of hemorrhagic stroke (64,65). Japanese cohort studies have found no association between dietary cholesterol intake and incidence of stroke, including hemorrhagic stroke (7,8,10,66). Interestingly, one study that had identified an inverse association between dietary cholesterol intake and incidence of stroke found that this association disappeared after adjusting for intake of animal protein and fat (66).…”
Section: Dietary Cholesterol 6-1 Dg (Lower Boundary)mentioning
confidence: 99%